Leptospirosis in China: Current Status, Insights, and Future Prospects - Wanqi Jiang; Shilei Zhang; Lianjie Ma; Meijing Zhang; Xufeng Xie; Tianbao Lv; Yue Ding; Wenlong Zhang; Yung-Fu Chang; Yongguo Cao (Zoonoses)
Leptospirosis is a re-emerging zoonotic disease that significantly impacts animals and human health worldwide. China has diverse climate types, providing a suitable environment for transmitting and surviving pathogenic Leptospira and its host animals. Despite the substantial reduction in the prevalence of leptospirosis, it continues to be a significant zoonotic disease of public health concern in China. This literature review aimed to provide a concise overview of the current status of leptospirosis in China, the findings from epidemiologic studies on leptospirosis, and the impact of animal and environmental factors on leptospirosis. Leptospirosis is commonly observed in subtropical and tropical cities in China, especially cities with ample water resources in the southern Yangtze River basin. Epidemiologic studies have identified Leptospira interrogans and L. borgpetersenii as the predominant pathogenic species responsible for leptospirosis in China. Leptospira serotypes prevalent in one part of China are related to the serotypes prevalent in the dominant local rodent species and these animals may threaten public health safety as carriers. Given the potential increase in the risk of leptospirosis due to extreme climate change, it is crucial to raise awareness among stakeholders and promote the adoption of a comprehensive approach to prevent and control the continuous transmission and sudden outbreaks of leptospirosis.